2021
DOI: 10.1108/bfj-07-2021-0727
|View full text |Cite
|
Sign up to set email alerts
|

The optimization of spray-drying process for the development of apricot powder using response surface methodology

Abstract: PurposeApricots are not only nutritionally-rich but also possess pharmacological significance owing to their high antioxidant activity, and they are rich in vitamins, fibers, bioactive phytochemicals and minerals. Because of its immense organoleptic characteristics, apricot juice (AJ) is well accepted; however, it has a limited shelf-life, thereby demanding it to be converted into other shelf-stable form. One of the approaches is converting this juice into dehydrated powder. Amongst the various dehydration tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…As already reported above, total phenolics reduced at higher temperature, Developing pear juice powder therefore, free radical scavenging activity decreased and thus lower antioxidant activity was reported (Loan et al, 2016). Bashir et al (2021) also observed similar findings. Mineral content.…”
Section: Physicochemical Propertiessupporting
confidence: 75%
See 4 more Smart Citations
“…As already reported above, total phenolics reduced at higher temperature, Developing pear juice powder therefore, free radical scavenging activity decreased and thus lower antioxidant activity was reported (Loan et al, 2016). Bashir et al (2021) also observed similar findings. Mineral content.…”
Section: Physicochemical Propertiessupporting
confidence: 75%
“…Further, due to the increased surface area through spray drying and exposure of fruit juice powders for oxidation and degradation, thus reducing lipid concentration (Patil et al, 2014). Similar results were obtained by Bashir et al (2021) for spray-dried apricot powder. Significantly (p < 0.05) lower fiber content was reported in SDPP (2.03 ± 0.05%) compared to PJ (2.18 ± 0.05%).…”
Section: Physicochemical Propertiessupporting
confidence: 59%
See 3 more Smart Citations